First Lower Cretaceous record of Podocarpaceae wood associated with dinosaur remains from Patagonia, Neuquén Province, Argentina - Gnaedinger, Silvia Cristina (2017)
The first Podocarpaceae wood record is described from the Mulichinco Formation (Valanginian, Lower Cretaceous), Neuquén Basin, Argentina. The specimen was directly associated with a middle caudal vertebra of a diplodocid sauropod dinosaur. A new species – Podocarpoxylon prumnopityoides – is proposed based on features that include the presence of abietinean wood type (tracheid radial pitting), plus podocarpoid (cupressoid type) and some dacrydioid (taxodioid type) cross-field pits, diffuse axial parenchyma and low rays. This combination of anatomical characters is comparable to both Prumnopitys and Podocarpus, whereas the type of pits in the cross-fields resembles some members of the extant Prumnopitys. This is the first unequivocal record of the Family Podocarpaceae in the Valanginian of South America and confirms the hypothesis that the divergence between the “Podocarpoid-Dacrydioid” and “Prumnopityoid” clades occurred earlier than the Early Cretaceous.